Influence of prolong curing, freeze thaw cycles on strength and compaction condition on water retention behaviour of bamboo biochar amended soils - Shailesh Kumar Yadav; Ramakrishna Bag (Scientific Reports)
Abstract Biochar has emerged as a promising soil amendment material, offering the potential to enhance mechanical and water retention properties. Geo-environmental structures constructed with biochar-amended soils (BAS) might experience a change in strength and water retention capacity due to extreme climactic changes, resulting in structural failures. The existing literature lacks a comprehensive study on the strength of BAS under prolonged curing, freeze-thaw cycles, and water retention behaviour for varying compaction conditions. The current study focused on addressing this research gap. Bamboo biochar (BB) was mixed with lean clay (CL) and silty sand (SM) in five different percentages (0%, 1%, 2%, 3.5% and 5% w/w) to prepare BAS specimens for unconfined compressive strength (UCS) and water retention tests. Results showed that UCS of CL soil increased up to 2% BB content but decreased thereafter, whereas it consistently decreased for SM soil with increasing BB content. Irrespective of the BB content, both soils consistently showed an increase in UCS with the curing period, which can be attributed to the enhanced bonding between the soil and BB, as well as the formation of stable aggregates. In contrast, the strength of both biochar-amended soils (BAS) decreased with the increase in freeze-thaw cycles, due to the expansion and contraction of ice within the specimen. The porous and hydrophilic nature of biochar (BB) increased the water retention capacity of both soils, with a more significant improvement observed in CL soil compared to SM soil, under both compacted and slurry conditions. Specimen compaction significantly decreased the gravimetric water content at the permanent wilting point in both soils. These variations were also evident in the microstructural analysis.